Agency in Action: Entrepreneurs' Networking Style and Initiation of Economic Exchange - Vissa, Balagopal (Organization Science, 2012)
This multimethod study investigates the effects of entrepreneurs' interpersonal networking style on the initiation of interorganizational exchange ties. I use inductive theorizing to make a distinction between interpersonal networking actions aimed at adding new contacts (network-broadening actions) versus managing existing contacts (network-deepening actions). I reason that because networking actions alter the cost-benefit calculus of using referrals, the extent to which entrepreneurs rely on referrals when searching for new exchange partners should vary with their networking actions. I then propose that entrepreneurs are likely to add fewer new exchange partners when they rely more on referrals to search. The empirical analysis employs a longitudinal design using data coded from the business cards of new contacts formed over a two-month period by a panel of Indian entrepreneurs operating business-to-business ventures. This study makes a theoretical contribution by identifying decision makers' networking style as a distinct mechanism shaping partner selection for their organization. Specifically, the study shows entrepreneurs using more network-deepening actions initiate fewer new economic exchanges, due (in part) to their increased reliance on referral-based search, whereas entrepreneurs using more network-broadening actions initiate more new economic exchanges due (in part) to their decreased reliance on referral-based search.